Socioeconomic Factors and Work Disability: Clues to Managing Chronic Pain Disorder - Robert W Teasell; Hillel M Finestone (Pain Research and Management)
Disability is a multifactorial phenomena in chronic pain disorders, as it is for other painful and nonpainful medical conditions. Socioeconomic factors are important determinants of disability, although this aspect of disability in chronic pain disorders is often ignored. Lower socioeconomic status has been shown to be associated with an increase in the frequency and severity of disability, and the rate of progression to disability in patients with chronic pain. Work disability in lower socioeconomic groups is associated with issues of physical work demands and work flexibility (ie, the ability to control the pace of work, take unscheduled breaks or engage in modified work). Workplace interventions, particularly in the subacute phase, that are geared to workers' limitations offer the best opportunity to reduce the current burden of disability. Where such work modifications are not available, disability will be problematic.